Makna Self-Healing pada Yayasan Rangkoel Care Indonesia - Bella Maulina; Atie Rachmiatie (Bandung Conference Series: Public Relations, 2023)
Abstract. This research was conducted based on the existence of a phenomenon regarding the existence of misinterpretation among the people, especially Generation Z regarding the meaning of "self-healing". The purpose of this research is to find out how Generation Z, especially members of the Rangkoel Care Indonesia Foundation, form a meaning of self-healing. This qualitative research uses a phenomenological approach, because this study aims to find meaning in a statement based on individual experiences of a phenomenon through in-depth research. By using the theory of motivation that was initiated by Alfred Schutz, regarding the formation of self-healing motives based on "because motives" and "in order motives". Data were obtained through in-depth in-depth interviews with research subjects, namely social & mental health activists. The results of the study showed that the informant felt that he was in a sincere/accepting situation in every situation, obtained calm, peace, and well-being within himself, then was able to know himself well, heal from the pain of past wounds, and do problem solving. Abstrak. Penelitian ini dilakukan berdasarkan dengan adanya fenomena mengenai adanya kesalahan pemaknaan di kalangan masyarakat khususnya Generasi Z mengenai pemaknaan “self-healing”. Tujuan dilakukan penelitian ini adalah untuk mengetahui bagaimana Generasi Z khususnya Anggota Yayasan Rangkoel Care Indonesia, dalam pembentukan sebuah makna self-healing. Penelitian kualitatif ini menggunakan metode pendekatan fenomenologi, karena penelitian ini bertujuan untuk mencari arti secara pernyataan berdasarkan pengalaman individu terhadap suatu fenomena melalui penelitian yang mendalam. Dengan menggunakan teori Motivasi yang dicetuskan oleh Alfred Schutz, tentang pembentukan motif self-healing berdasarkan “because motif" dan "in order motif”. Data diperoleh melalui in-depth interview mendalam dengan subjek penelitian, yaitu aktivis kegiatan sosial & mental health. Hasil penelitian menunjukan bahwan informan merasa sudah ada disituasi ikhlas/menerima dalam setiap keadaan, memperoleh adanya ketenangan, ketentraman, dan kesejahteraan didalam dirinya, lalu bisa mengenal diri sendiri dengan baik, penyembuhan dari rasa sakit luka dimasa lalu, dan melakukan problem solving.